Personal social networks as informal social control in unaccompanied minors and foreign young people. - Casado Patricio, Elena (My University, 2021)
This investigation explores the composition of the social networks of some samples of unaccompanied foreign minors and young foreigners ex-ward. The increase in the number of unaccompanied foreign minors arriving in Spanish territory, the importance of social capital in migration as a resource of informal social control and the lack of research that analyzes their social networks makes the research presented here relevant. Specifically, it is verified how the composition of the networks varies and decisions are the main sources of resources of both samples in situations of vulnerability. The results showed, through a quantitative methodology and graphs, that the networks are mainly made up of professionals and volunteers from the social sphere and that the networks of minors are more extensive than that of former foster youth.
Keywords: Menores de edad - Redes sociales; Social networks; Minors; Foreigners; Vulnerability